Competitive analysis of public urban transport. (10th May 2019) - Ogorodnikova, Ekaterina; Sidorenko, Alexander; Plakhin, Andrey
The paper presents the results of a study of the level of competitiveness of public urban transport using the example of Ekaterinburg (Russian Federation). The study methodology assumes a two-stage assessment by consumers of public transport types in Ekaterinburg. The two stages are competitiveness comparative assessment and its increasing trend ranking. The strategic ways of overcoming the current situation in the medium term have been determined.